The teacher as examiner of L2 oral tests: A challenge to standardization. (April 2018) - Sundqvist, Pia; Wikström, Peter; Sandlund, Erica; Nyroos, Lina
The present paper looks at the issue of standardization in L2 oral testing. Whereas external examiners are frequently used globally, some countries opt for test-takers' own teachers as examiners instead. In the present study, Sweden is used as a case in point, with a focus on the mandatory, high-stakes, summative, ninth-grade national test in English (speaking part). The national test has the typical characteristics of standardized tests and its main objective is to contribute to equity in assessment and grading on a national level. However, using teachers as examiners raises problems for standardization. The aim of this study is to examine teachers'/examiners' practices and views regarding four aspects of the speaking test – test-taker grouping, recording practices, the actual test occasion, and examiner participation in students' test interactions – and to discuss findings in relation to issues concerning the normativity and practical feasibility of standardization, taking the perspectives of test-takers, teachers/examiners, and test constructors into account. In order to answer research questions linked to these four aspects of L2 oral testing, self-report survey data from a random sample of teachers ( N = 204) and teacher interviews ( N = 11) were collected and quantitative data were analyzed using inferential statistics. Survey findings revealed that despite thorough instructions, teacher practices and views vary greatly across all aspects, which was further confirmed by interview data. Three background variables – teacher certification, work experience, gender – were investigated to see whether they could provide explanations. Whereas certification and gender did not contribute significantly to explaining the findings, work experience bore some relevance, but effect sizes were generally small. The study concludes that using teachers as examiners is a well-functioning procedure in terms of assessment for learning, but raises doubts regarding assessment of learning and standardization; a solution for test authorities could be to frame the test as non-standardized.